2015
DOI: 10.5114/kitp.2015.54453
|View full text |Cite
|
Sign up to set email alerts
|

Artificial aortic valve dysfunction due to pannus and thrombus – different methods of cardiac surgical management

Abstract: IntroductionApproximately 60 000 prosthetic valves are implanted annually in the USA. The risk of prosthesis dysfunction ranges from 0.1% to 4% per year. Prosthesis valve dysfunction is usually caused by a thrombus obstructing the prosthetic discs. However, 10% of prosthetic valves are dysfunctional due to pannus formation, and 12% of prostheses are damaged by both fibrinous and thrombotic components. The authors present two patients with dysfunctional aortic prostheses who were referred for cardiac surgery. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…BMHV dysfunction may appear at anytime between 1 hour and 20 years (median: 44.5 months) following the primary valve replacement . Its reported incidence rate ranges between 0.1% and 6.0% and it represents a major life‐threatening event associated with a significantly high mortality rate in emergency (28.6%) . BMHV dysfunction is due to thrombus formation (41%), to pannus growth (38%) or to both (21%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMHV dysfunction may appear at anytime between 1 hour and 20 years (median: 44.5 months) following the primary valve replacement . Its reported incidence rate ranges between 0.1% and 6.0% and it represents a major life‐threatening event associated with a significantly high mortality rate in emergency (28.6%) . BMHV dysfunction is due to thrombus formation (41%), to pannus growth (38%) or to both (21%).…”
Section: Introductionmentioning
confidence: 99%
“…Other cases may include: improper valve orientation, a missing leaflet or excessively long knots during surgery. An excellent review on the topic can be found in Huang et al and the related references . Although there is a consensus that patients with BMHV dysfunction due to pannus formation should be reoperated, the optimal management of patients with BMHV dysfunction due to thrombus formation remains controversial .…”
Section: Introductionmentioning
confidence: 99%